Cloud Gate Dance Theatre Review - Roy, Sanjoy (Dance Books Ltd., Alton,Hampshire (UK), 2002)
PALABRAS CLAVE: Lin Hwai-min, Cloud Gate Dance Theatre, Taiwan, contemporary dance, Moon Water.
Dentro del apartado "Dance Now. Water Works. Raining choreography at the Wells".